PEMBUATAN APLIKASI CHATBOT UNTUK CUSTOMER SERVICE PADA RUMAH SAKIT UMUM DAERAH CICALENGKA - Muhammad Rifqy (2023)
The Cicalaengka Regional General Hospital (RSUD) is a health service agency that serves the community in the Bandung area, especially around the Cicalengka subdistrict which makes the Cicalengka Regional General Hospital serve many patients in its daily operations. The Cicalengka Regional General Hospital still does not have a responsive customer care system and the website that is owned by the Cicalengka Regional General Hospital is deemed less informative in providing information services to patients or prospective patients from the Cicalengka Regional General Hospital. Therefore, an application service is needed that provides customer service to fulfill requests for information services for patients and prospective patients as a form of answer to the problems experienced by the Cicalengka Regional General Hospital. The purpose of this research is to design and build a customer service application with a web-based chatbot that can help the Cicalengka General Hospital in providing information services to patients. This research uses the waterfall method as the development method for applications with javascript and php as programming languages and MySQL as a database for creating chatbot applications for customer care. The result of this research is a customer care application using chatbots as a support in applications made. Chatbot applications for customer service are built to help hospitals in supporting their health service processes. The application also makes it easier for patients to find the information needed